Financial and Economic Stability of Energy Sector Enterprises as a Condition for Poland’s Energy Security—Legal and Economic Aspects - Adam Zając; Rafał Balina; Dariusz Kowalski (Energies, 2023)
The energy security of each country is one of the main factors of its proper functioning. Currently, in the era of problems related to energy security resulting from, among other things, the war in Ukraine, this topic is particularly important. This article presents issues related to Poland’s energy security, understood as the financial and economic stability of enterprises operating in the energy industry. This stability is considered in two aspects: macroeconomic, where the focus is mainly on the aspect of state intervention in market processes; and microeconomic, where factors determining the financial security of energy enterprises were identified, including internal and external factors affecting the functioning of these entities. In order to achieve the assumed research goals, the analysis of the indicated problems was based on non-reactive research, consisting in the assessment of the available information. It included studies of normative acts, official statistical data, industry reports and analyses, as well as data obtained in the form of a public information request. Two basic research methods were used in the work—dogmatic–legal and comparative analyses. The identification of factors affecting the security of companies in the sector was carried out on the basis of data on the entire energy sector in Poland for the years 2015–2021 on a semi-annual basis. Vector-autoregressive models were used for the analysis. As a result of the analyses, it was established that market failures and public safety are the premises justifying the public financing of enterprises in the electricity generation, transmission, distribution and trade sectors. At the same time, the conducted research showed that the level of financial security of energy enterprises in Poland was affected by the ratio of the value of goods and materials sold to net sales revenue, as well as the level of EBIT (earnings before deducting interest and taxes) margin, and among external factors, the level of GDP (gross domestic product), CPI (consumer price index) and Crude Oil were important.